Development of setup for human energy expenditure rate for ergonomic design of thresher - J, SRIKANTHNAIK; SHARMA, PRAMOD KUMAR; KUSHWAHA, H L (The Indian Journal of Agricultural Sciences, 2021)
This paper presents results of study on response of the most significant design parameter to optimize rotary power generation. From the experiment results it was found that at all mechanical output the step height of 25.96 cm was found best. At mechanical output 37.5W of step height 25.96 cm, the working heart rate, oxygen consumption rate, energy expenditure rate and body part discomfort score are 113.61 beat/min, 0.61 l/min, 12.72 kj/min (211.99 W) and 17.25 respectively. Based on this energy expenditure rate, the capacity of the solar module was selected as 200W.